Persepsi Wajib Pajak UMKM Terhadap Kewajiban Perpajakan (Studi Pada UMKM di Eks Karisidenan Surakarta) - Hanung Triatmoko; Juliati Juliati; Sri Suranta; Trisninik Ratih Wulandari; Renata Zoraifi (ITB AAS INDONESIA, 2021)
This study aims to assess the perceptions of MSME taxpayers who are in the Karisidenan Surakarta area on tax obligations. MSMEs are a driver of increasing economic growth in the present era. Solo is one of the cities that is famous for the growth of MSMEs because culinary, handicraft, and clothing entrepreneurs have started to appear in Karisidenan Surakarta. Ideally, an increase in the number of MSMEs will also be followed by an increase in the amount of taxes that will be received by local and central governments. Income Tax (PPh) and Value Added Tax (PPN) are two central taxes which should also increase with the growth of MSMEs. The perception of UMKM taxpayers towards taxation obligations is certainly important to research because negative perceptions of taxes will result in decreased tax revenues so that these perceptions need to be improved with better socialization from the Directorate General of Taxes. This study will examine the perceptions of taxpayers related to NPWP ownership, SPT reporting and tax payments. The method used is a quantitative method by distributing questionnaires to samples of MSMEs in Karisidenan Surakarta. The sampling method used was purposive sampling and the analysis used was linear regression analysis. This research is expected to provide benefits to the government in making policies to increase tax revenue.